Beyond Autoantibodies: Biologic Roles of Human Autoreactive B Cells in Rheumatoid Arthritis Revealed by RNA-Sequencing - Mahendra, Ankit; Yang, Xingyu; Abnouf, Shaza; Adolacion, Jay R.T.; Park, Daechan; Soomro, Sanam; Roszik, Jason; Coarfa, Cristian; Romain, Gabrielle; Wanzeck, Keith; Bridges, S. Louis; Aggarwal, Amita; et al. (Arthritis and Rheumatology, 2019)
Objective: To obtain the comprehensive transcriptome profile of human citrulline-specific B cells from patients with rheumatoid arthritis (RA). Methods: Citrulline- and hemagglutinin-specific B cells were sorted by flow cytometry using peptide–streptavidin conjugates from the peripheral blood of RA patients and healthy individuals. The transcriptome profile of the sorted cells was obtained by RNA-sequencing, and expression of key protein molecules was evaluated by aptamer-based SOMAscan assay and flow cytometry. The ability of these proteins to effect differentiation of osteoclasts and proliferation and migration of synoviocytes was examined by in vitro functional assays. Results: Citrulline-specific B cells, in comparison to citrulline-negative B cells, from patients with RA differentially expressed the interleukin-15 receptor α (IL-15Rα) gene as well as genes related to protein citrullination and cyclic AMP signaling. In analyses of an independent cohort of cyclic citrullinated peptide–seropositive RA patients, the expression of IL-15Rα protein was enriched in citrulline-specific B cells from the patients’ peripheral blood, and surprisingly, all B cells from RA patients were capable of producing the epidermal growth factor ligand amphiregulin (AREG). Production of AREG directly led to increased migration and proliferation of fibroblast-like synoviocytes, and, in combination with anti–citrullinated protein antibodies, led to the increased differentiation of osteoclasts. Conclusion: To the best of our knowledge, this is the first study to document the whole transcriptome profile of autoreactive B cells in any autoimmune disease. These data identify several genes and pathways that may be targeted by repurposing several US Food and Drug Administration–approved drugs, and could serve as the foundation for the comparative assessment of B cell profiles in other autoimmune diseases.
Keywords: Arthritis, Rheumatoid; Autoantibodies; B-Lymphocytes; Cytokines; ErbB Receptors; Humans; Leukocytes, Mononuclear; Receptors, Interleukin-15; Sequence Analysis, RNA; Signal Transduction; Transcriptome